METHODS OF ENHANCING SPEAKING SKILLS OF STUDENTS THROUGH STORY BASED LEARNING - Makhmudov Islombek Muhiddin o’g’li (Modern American Journals, 2025)
This article explores effective pedagogical strategies to enhance students’ speaking skills through the application of story-based learning, specifically using picture composition. The research focuses on how guided observation of visuals, structured storytelling techniques, use of sequencing and transitional phrases, as well as the integration of emotional expression can significantly contribute to the development of speaking fluency. It highlights the benefits of using pictures as cognitive and creative prompts that help learners to organize thoughts, build narrative coherence, and present ideas confidently. Furthermore, the study emphasizes the importance of relatable content, logical sequencing, and authenticity in storytelling. Practical classroom-based examples and exercises are used to demonstrate the method’s effectiveness.
Keywords: Story-based learning, speaking skills, picture composition, storytelling, observation.